A Novel Retrovirus (Gunnison’s Prairie Dog Retrovirus) Associated With Thymic Lymphoma in Gunnison’s Prairie Dogs in Colorado, USA - Molly D. Butler; Karen Griffin; Connie D. Brewster; Marylee L. Kapuscinski; Mark D. Stenglein; Daniel W. Tripp; Sandra L. Quackenbush; Karen A. Fox (Viruses, 2020)
As part of research and wildlife disease surveillance efforts, we performed necropsy examinations of 125 free-ranging (n = 114) and captive (n = 11) prairie dogs in Colorado from 2009 to 2017. From these cases, we identified three cases of thymic lymphoma in free-ranging Gunnison’s prairie dogs (Cynomys gunnisoni), and we identified a novel retroviral sequence associated with these tumors. The viral sequence is 7700 nucleotides in length and exhibits a genetic organization that is consistent with the characteristics of a type D betaretrovirus. The proposed name of this virus is Gunnison’s prairie dog retrovirus (GPDRV). We screened all 125 prairie dogs for the presence of GPDRV using PCR with envelope-specific primers and DNA extracted from spleen samples. Samples were from Gunnison’s prairie dogs (n = 59), black-tailed prairie dogs (Cynomys ludovicianus) (n = 40), and white-tailed prairie dogs (Cynomys leucurus) (n = 26). We identified GPDRV in a total of 7/125 (5.6%) samples including all three of the prairie dogs with thymic lymphoma, as well as spleen from an additional four Gunnison’s prairie dogs with no tumors recognized at necropsy. None of the GPDRV-negative Gunnison’s prairie dogs had thymic lymphomas. We also identified a related, apparently endogenous retroviral sequence in all prairie dog samples. These results suggest that GPDRV infection may lead to development of thymic lymphoma in Gunnison’s prairie dogs.